Biochar: An emerging recipe for designing sustainable horticulture under climate change scenarios - Zulfiqar, Faisal; Moosa, Anam; Nazir, Muhammad Mudassir; Ferrante, Antonio; Ashraf, Muhammad; Nafees, Muhammad; Chen, Jianjun; Darras, Anastasios; Siddique, Kadambot H.M. (Frontiers in Plant Science, 2022)
The interest in sustainable horticulture has recently increased, given anthropogenic climate change. The increasing global population will exacerbate the climate change situation induced by human activities, elevating global food demands and the vulnerability of horticultural systems, with severe concerns related to natural resource availability and usage. Sustainable horticulture involves adopting eco-friendly strategies to boost yields while maintaining environmental conservation. Biochar (BC), a carbon-rich material, is widely used in farming to improve soil physical and chemical properties and as an organic substitute for peat in growing media. BC amendments to soil or growing media improve seedling growth, increase photosynthetic pigments, and enhances photosynthesis, thus improving crop productivity. Soil BC incorporation improves abiotic and biotic stress tolerance, significant constraints to horticulture. BC application also improves disease control to an acceptable level or enhances plant resistance against pathogens. Moreover, BC amendment in contaminated soil decreases the uptake of potentially hazardous metals, thus minimizing harmful effects on humans. This review summarizes the most recent knowledge related to BC use in sustainable horticulture, including the effect of BC on enhancing horticultural crop production and inducing resistance to major abiotic and biotic stresses. We also discuss major gaps and future directions for exploiting BC technology.